A Case of Chronic Pancreatic Insufficiency Due to Valproic Acid in a Child. (1st February 2001) - Cooper, Mary Anne; Groll, Aubrey
Abstract : A 14-year-old child treated with valproic acid over several years for a seizure disorder developed abdominal pain with radiological evidence of acute pancreatitis. The association with valproic acid was not recognized, and the child continued to take the drug. The patient eventually developed steatorrhea and weight loss that improved with pancreatic enzyme replacement. Radiological evaluation showed an atrophic pancreas. Without evidence of other etiological factors, valproic acid by itself appeared to be the cause of chronic pancreatitis with exocrine pancreatic insufficiency in this patient.